The Jellybeans and the big art adventure - Numeroff, Laura Joffe (Abrams Books for Young Readers, 2012)
The Jelly Beans--four friends who like to do such different things as paint, play soccer, read, and dance--paint a mural on an outside wall of Mrs. Petunia Dinkley-Sneezer's candy shop that depicts them each doing what they love best.